Impact of Body Weight Dynamics Following Intentional Weight Loss on Fracture Risk: Results from The Action for Health in Diabetes Study. (25th October 2018) - Beavers, Kristen M; Neiberg, Rebecca H; Johnson, Karen C; Davis, C Hunter; Casanova, Ramon; Schwartz, Ann V; Crandall, Carolyn J; Lewis, Cora E; Pi‐Sunyer, Xavier; Kritchevsky, Stephen B; ,
Abstract: The purpose of this study is to explore the impact of body weight change following intentional weight loss on incident fracture and bone mineral density (BMD) in overweight and obese adults with diabetes. A total of 1885 individuals with type 2 diabetes (baseline age: 58.5 ± 6.7 years, 58% women, body mass index: 35.7 ± 6.0 kg/m 2 ) who participated in the Look AHEAD study and lost any weight 1 year after being randomized to an intensive lifestyle intervention were assessed. Body weight was measured annually and participants were categorized as weight regainers, weight cyclers, or continued losers/maintainers based on a ±3% annual change in weight from year 1 to year 4. Adjudicated overall fracture incidence was captured from years 4 through 13 (median follow‐up duration 11.5 years). Hip and spine BMD was assessed in a subset of participants at baseline, year 4 ( n  = 468), and year 8 ( n  = 354), using dual‐energy X‐ray absorptiometry. Cox proportional hazards and linear regression models, adjusted for relevant covariates, were performed for fracture and BMD outcomes, respectively. Fifty‐eight percent, 22%, and 20% of participants were classified as weight regainers, weight cyclers, and continued losers/maintainers, respectively; and 217 fractures (men n  = 63; women n  = 154) were recorded during the follow‐up period. There were no statistically significant differences in total incident fracture rates for weight regainers (HR [95% CI]: 1.01 [95% CI, 0.71 to 1.44]) or weight cyclers (HR [95% CI]: 1.02 [95% CI, 0.68 to 1.53]) when compared to continued losers/maintainers ( p  = 0.99). Similarly, follow‐up BMD estimates did not significantly vary by weight pattern group, although consistent trends for lowered BMD in the hip region were noted for continued losers/maintainers and weight cyclers compared with weight regainers. Patterns of weight change in the 3 years following 1 year of intentional weight loss were not associated with subsequent fracture or significantly reduced BMD in this cohort of overweight and obese adults with type 2 diabetes. © 2018 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.